Haglund’s Syndrome: endoscopic or open treatment? - Lughi, Marcello (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work. With the term “Haglund›s syndrome” we define a condition characterized clinically by pain at the insertion of Achille›s tendon and, anatomopathologically, due to the presence of retrocalcaneal bursitis and at times associated with an insertional Achille›s tendinopathy. The aim of the work is to correlate the most reliable and reproducible treatment possible to the aforementioned variables of Haglund›s syndrome. Methods. The classic syndromic picture is characterized by pain caused by retrocalcaneal bursitis. In some cases, symptoms of insertional tendinopathy are associated with bursitis pain. In those frameworks where symptoms were mainly exacerbated by the bursitis inflammation we have used an endoscopic technique for the resection of the underlying bone deformation and the bursa. An open technique, described in the literature as bridge sutures, was used for those patients with tendinopathic problems. While a homologous PRP unit was infiltrated in patients with degenerative insertional tendinopathy. Results. The group of patients that participated to the study was heterogeneous in age and functional requirements therefore presenting different anatomopathological characteristics. For these reasons considerations with correct statistical meaning are not possible. Despite different post-operative programs, patients demonstrated optimal clinical and functional recovery. There were no local neurological or skin complications. Conclusions. Haglund›s syndrome can have different clinical and anatomopathological patterns where conservative treatment is unsuccessful surgical solutions must be adopted. The latter have shown to be reliable and reproducible with a very low rate of complications. (www.actabiomedica.it)